The Effect Of Remote Working On Productivity And Work-Life Balance With Employee Engagement As A Mediating Variable Among Millennial Employees In D.I. Yogyakarta - Nukadea Septia Agung; Andriyastuti Suratman (International Journal of Economics, Business and Innovation Research, 2026)
The The development of digital technology has driven changes in organizational work patterns through the implementation of remote working, particularly among millennial employees who prioritize flexibility and work–life balance. However, empirical findings regarding the impact of remote working on employee productivity and work–life balance remain inconsistent. Therefore, this study aims to examine the effect of remote working on employee productivity and work–life balance with employee engagement as a mediating variable among millennial employees in the Special Region of Yogyakarta. This study employs a quantitative approach using a survey method. Data were collected through an online questionnaire utilizing a five-point Likert scale and analyzed using statistical analysis techniques. The respondents consist of millennial employees who implement a remote working system in the Special Region of Yogyakarta. The results indicate that remote working has a positive effect on employee engagement. Furthermore, employee engagement positively influences employee productivity and work–life balance and serves as a mediating variable that strengthens the relationship between remote working and both outcomes. These findings suggest that the effectiveness of remote working largely depends on the level of employee engagement